2005
DOI: 10.1007/s00428-005-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Claudin expression in Barrett's esophagus and adenocarcinoma

Abstract: Claudins (CLDNs) are key molecules in cell adhesion, polarity, and control of paracellular solute transport. Several studies suggested that changes in claudin pattern have a role in cancer development. This study aimed to detect alterations in CLDN 1, 2, 3, 4, and 7 expression patterns in Barrett's esophagus (BE) and adenocarcinoma (ACC) compared with that in foveolar epithelium (FOV), normal squamous epithelium (SQ), and squamous cell carcinoma (SQCC). One hundred twenty five surgically or endoscopically remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 39 publications
3
51
3
1
Order By: Relevance
“…[17][18][19] In line with this hypothesis complex alterations of TJ expression in BE and BC compared to esophageal squamous epithelium have been observed: claudin-1 and claudin-5 are downregulated in BE 19,20 whereas for claudin-2, -3, -4 and -7 an upregulation has been noted, in particular in highgrade IN and BC. 17,19,21 These data suggest that downregulated TJ proteins might facilitate inhibitory functions, whereas upregulated TJs may promote the progression of BE. However, despite these findings a detailed understanding of how TJ contribute to malignant transformation and disease progression in BE and BC, is still lacking.…”
Section: Introductionmentioning
confidence: 86%
“…[17][18][19] In line with this hypothesis complex alterations of TJ expression in BE and BC compared to esophageal squamous epithelium have been observed: claudin-1 and claudin-5 are downregulated in BE 19,20 whereas for claudin-2, -3, -4 and -7 an upregulation has been noted, in particular in highgrade IN and BC. 17,19,21 These data suggest that downregulated TJ proteins might facilitate inhibitory functions, whereas upregulated TJs may promote the progression of BE. However, despite these findings a detailed understanding of how TJ contribute to malignant transformation and disease progression in BE and BC, is still lacking.…”
Section: Introductionmentioning
confidence: 86%
“…Immunohistochemical analysis indicated that CLDN2 expression was increased in Barrett's esophageal cancer and that CLDN3 and CLDN4 were up-regulated in Barrett's esophagus and adenocarcinoma [40]. In contrast, another report showed upregulation of CLDN2 and CLDN3 and downregulation of CLDN1 in Barrett's esophagus [41].…”
Section: Involvement Of Tj Proteins In Diseases Gastroesophageal Reflmentioning
confidence: 95%
“…Few studies have analyzed TJ protein expression in esophageal squamous cell carcinoma; an increase in CLDN1 immunohistochemical staining, and no change in CLDN4 and CLDN7 staining, have been reported [40]. Immunohistochemical analysis indicated that CLDN2 expression was increased in Barrett's esophageal cancer and that CLDN3 and CLDN4 were up-regulated in Barrett's esophagus and adenocarcinoma [40].…”
Section: Involvement Of Tj Proteins In Diseases Gastroesophageal Reflmentioning
confidence: 99%
“…Several reports suggested that the claudins were correlated with esophageal cancer carcinogenesis. Significant increase in claudin-1 expression was detected in esophageal squamous cell carcinoma as compared with that in esophageal squamous epithelium (6), and reduced expression of claudin-1 was significantly associated with histological differentiation of the tumor (28). However, the relationship between the claudins and recurrence status of esophageal cancer has not yet 47-82) years.…”
mentioning
confidence: 99%
“…The claudins have been suggested to be associated with carcinogenesis and tumor progression. Alteration of claudins has been detected in carcinomas of the esophagus (6,13,15,23,28), colorectum (14,19), and other cancers (16,21,24), suggesting that the claudins are involved in the process of carcinogenesis (20).…”
mentioning
confidence: 99%